Analisis Implementasi UU TPKS dalam Sistem Pendidikan dan Standar Profesi Kebidanan di Indonesia - Inna Noor Inayati (Lembaga Pengembangan Kinerja Dosen, 2026)
Indonesia is currently experiencing an emergency situation regarding sexual violence, which compromises national social resilience. The enactment of the Sexual Violence Crimes Law (UU TPKS) creates new legal mandates for healthcare professionals. Midwives, serving as frontline providers in primary care and remote areas, act as the first professional contact for survivors, yet they lack adequate legal certainty regarding medico-legal duties and preparedness within the midwifery educational framework. Objectives: This study aims to analyze the regulatory synchronization concerning the limited medico-legal authority of midwives in implementing the UU TPKS and to formulate reconstruction strategies for professional standards and the national midwifery curriculum. Methods: This normative juridical (doctrinal) research utilizes statute, conceptual, analytical, and comparative approaches. Data analysis was conducted qualitatively-normatively through systematic and teleological interpretations, evaluated using coherence and prescriptive frameworks. Results: The study reveals a significant disharmony of norms between the UU TPKS and Minister of Health Regulation (Permenkes) No. 2 of 2025, which imposes bureaucratic barriers on safe abortion access for rape victims. Additionally, the Midwife Professional Standards (Kepmenkes No. 320/2020) fail to integrate basic clinical forensic authorities, compounded by a national techno-centric curriculum that overlooks Trauma-Informed Care (TIC). Conclusions: Legal certainty for midwives and comprehensive justice for survivors can only be accomplished by reconstructing inclusive competency standards, eliminating administrative boundaries through the